Assessment of professional self‐efficacy in psychological interventions and psychotherapy sessions: Development of the Therapist Self‐Efficacy Scale (T‐SES) and its application for eTherapy. Issue 11 (26th May 2022) - Gori, Alessio; Topino, Eleonora; Brugnera, Agostino; Compare, Angelo
Abstract: Objective: This study aimed to develop the Therapist Self‐Efficacy Scale (T‐SES), and test its validity in a sample of Italian mental health therapists, to assess their professional self‐efficacy concerning their practice of eTherapy in a synchronous video‐based setting. Methods: A sample of 322 Italian mental health professionals (37.6% psychologists, 62.4% psychotherapists; M age  = 38.48, SD  = 8.509) completed an online survey. Results: The T‐SES showed a clear, one‐factor structure with good psychometric properties. Significant associations were found with insight orientation, general self‐efficacy, self‐esteem, and personality traits of openness, conscientiousness, and agreeableness. The results showed no differences between psychologists and psychotherapists, or differences based on years of experience. Conclusion: The T‐SES is an agile and versatile self‐report measure for mental health professionals to assess their self‐efficacy concerning their therapeutic activity, which can provide information for tailoring training for eTherapy.